Ρ(x) = (a/2 - 1)·x^2 - 2·((2 - a)/3)·x + a
0 = (a/2 - 1)·1^2 - 2·((2 - a)/3)·1 + a
0 = (a/2 - 1) - (4/3 - 2·a/3) + a
0 = 13·a/6 - 7/3----> a = 14/13
----------------------------------------------
P(1)= (a/2 - 1)·1^2 - 2·((2 - a)/3)·1 + a
P(-1) = (a/2 - 1)·(-1)^2 - 2·((2 - a)/3)·(-1) + a
P(1)= (13·a - 14)/6
P(-1)= (5·a + 2)/6
P(1)=-P(-1)
(13·a - 14)/6 = - (5·a + 2)/6
(13·a - 14)/6 + (5·a + 2)/6 = 0
3·a - 2 = 0----> a = 2/3
-----------------------------------------------
Ρ(2) = (a/2 - 1)·2^2 - 2·((2 - a)/3)·2 + a = R
Ρ(2) = (13·a - 20)/3 = R
Th Ruffini:
(13·a - 20)/3 = 0---> a = 20/13
------------------------------------------------
Ρ(-1) = (a/2 - 1)·(-1)^2 - 2·((2 - a)/3)·(-1) + a = R
Ρ(-1) = (5·a + 2)/6 = R
Th del Resto:
(5·a + 2)/6 = 1---> a = 4/5